Os saberes do corpo: a “medicina caseira” e as práticas populares de cura no Ceará (1860-1919) - Gadelha, Georgina da Silva (2007)
The actual dissertation aims to reflect about the popular practices of healing and medical science in the state of Ceará, Brazil, during the second half of the 19th century. The book “Medicina Caseira” (organized in 1919 by Juvenal Galeno) was taken as analysis source and object, because it showed itself as a disturbing production, since it deals with homemade recipes, popular practices of healing during that period, in a moment that medical science in Ceará was beginning to structure itself as a legitimating science of health and disease. Througt the process of investigation, some points of convergence and divergence were found out among the practices of healing that are related with scientific and popular knowledge. Such a perception allowed us to think about how these popular practices of healing are found at the present time and even, in some cases, were appropriated into the scientific medicine in its processo of affirmation while intervening practice in the social arena and in its search of institutionalization.